“An Inner Comprehension of the Pueblo Indian’s Point of View”: Carl Gustav Jung’s 1925 Visit to Taos, New Mexico - Maszewski, Zbigniew (Text Matters: A Journal of Literature, Theory and Culture, 2015)
Carl Jung paid a short visit to Taos, New Mexico, in January 1925. A brief account of his stay at the Pueblo appeared in Memories, Dreams, Reflections, edited by Aniela Jaffe in 1963. Remembering his conversations with Mountain Lake (Antonio Mirabal), Jung wrote of the confrontation between the “European consciousness,” or the “European thought,” with the Indian “unconscious.” My article provides a reading of Jung’s text as a meeting ground of the aesthetic, emotional, visionary and of the analytical, rational, explanatory. Like many other European and Anglo-American visitors to Taos Pueblo, Jung rediscovers its capacity to mirror the inner needs of the visitor; he examines the significance of the encounter with the Southwestern landscape and with the Pueblo Indians’ religious views in terms of self-reflection and of the return to the mythical. As Carl Jung’s “inner comprehension” of the Pueblo Indian’s philosophy is mediated through language, aware both of its desire and its inability to become liberated from the European perspectives, Mountain Lake’s attitude towards his visitor from Switzerland remains ultimately unknown; Mountain Lake does, however, communicate his readiness to assume the archetypal role of a teacher and a spiritual guide whose insights reach beyond the confines and mystifications of language. According to Jung’s account, during this brief encounter of the two cultures, he and his Indian host experienced a sense of satisfaction and fulfillment, the sources of which, as they both understood them in their own individual ways, resided in the comprehension of universal sharing.